TATA KELOLA PERKEBUNAN KELAPA SAWIT SWADAYA DAN PRODUKTIVITAS YANG BERKELANJUTAN DI KECAMATAN TANDUN KABUPATEN ROKAN HULU PROPINSI RIAU - Risman, Risman (Jurnal Ekonomi Bisnis Kompetif, 2025)
Independent oil palm plantations are an important sector in the economy of the community in Tandun District, Rokan Hulu Regency, but are still faced with challenges related to less than optimal governance. This article aims to analyze the governance of independent oil palm plantations and productivity. Good governance is considered key in improving production efficiency and sustainability, while poor governance can hinder the achievement of optimal results. This study used a qualitative approach with a survey method of independent oil palm farmers in several plantation areas in Tandun District, Rokan Hulu Regency. The results showed that there is a significant positive relationship between good governance and increased productivity. Factors such as consistent monitoring, use of appropriate technology, fertilization and managerial capacity building are instrumental in increasing independent oil palm production yields.Keywords: Governance, independent oil palm plantation, productivity, sustainability.